Trade openness, real exchange rate, gross domestic investment and growth in Indonesia - Yusoff, Mohammed (Sage Publications, 2014)
This study examines the relationships among economic growth, domestic investment, real exchange rate and trade openness in Indonesia using the Johansen cointegration test and Granger causality test. The results suggest that there exists a long-run relationship among the variables. All the estimated coefficients of the long-run equation have the correct positive signs and significant at least at the 5 per cent level. Specifically, in the long run, a 1 per cent increase in trade openness leads to about 26.5 per cent increase in Indonesian real GDP, a 1 per cent increase in domestic investment will spur real GDP by 1.8 per cent, and a 1 per cent depreciation of the rupiah raises real GDP by about 6.4 per cent. The results from the Granger causality test suggest that all the variables affect real GDP in the short run. Both trade openness and gross domestic investment cause growth unidirectionally in the short run, but feedback occurs between growth and the real exchange rate. The evidences suggest that trade openness, gross domestic investment and the exchange rate are important determinants of economic growth and therefore policy makers should seriously take these variables into account in their policy construct in order to achieve sustained economic growth in Indonesia. Specifically, Indonesia should liberalise foreign trade, improve the domestic investment climate and maintain exchange rate stability.